Micron-sized porous sodium ferrous sulfate / carbon composite cathode material and sodium-ion or sodium battery produced therefrom

The micron-sized porous sodium ferrous sulfate/carbon composite electrode material addresses the limitations of traditional cathode materials by providing enhanced structural stability and conductivity, leading to high-energy and high-power sodium ion batteries with long cycle life and low cost.

JP2024546368AActive Publication Date: 2024-12-20ZHENGZHOU UNIV

Patent Information

Application Number
JP2024529880
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-16
Filing Date
2021-12-22
Publication Date
2024-12-20
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

Traditional sodium ion battery cathode materials face challenges with poor mechanical properties, severe polarization at higher rates, low specific discharge capacity, and poor cycle stability, limiting their application in large-scale energy storage systems.

Method used

A micron-sized porous sodium ferrous sulfate/carbon composite positive electrode material is developed through coprecipitation and solid-state calcination methods, featuring a porous structure with densely accumulated primary particles coated with amorphous carbon and a thin layer of reduced graphene, optionally doped with metal elements to enhance stability and conductivity.

Benefits of technology

The composite material improves structural stability, reduces polarization, and enhances ion diffusivity, resulting in sodium ion batteries with high energy and power densities, long cycle stability, and low electrode cost, suitable for large-scale energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546368000001_ABST
    Figure 2024546368000001_ABST
Patent Text Reader

Abstract

The objective of the present invention is to provide a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material and a sodium-ion battery or sodium battery produced therefrom. SOLUTION: The composite material of the present invention includes a sodium ferrous sulfate / carbon composite material with and / or without metal doping elements, which is prepared by coprecipitation and solid-state calcination, and the particle size is 2-30 nm, has a porous structure, and is composed of densely packed 80-200 nm primary particles densely covered with amorphous carbon, and the surface of the micron particles is covered with a thin layer of reduced graphene to form a three-dimensional conductive network. The micron-sized particle positive electrode material has a high tap density, which is helpful in increasing the volumetric energy density of the battery, and the material has the advantages of abundant raw material reserves, low cost, high operating voltage, good rate characteristics and cycle stability as the positive electrode of sodium ion batteries or sodium batteries, and the preparation process of the material is simple. The sodium ion batteries or sodium batteries of the present invention have the advantage of high energy density and have the prospect of broad market application.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of cathode materials for sodium ion batteries, in particular to a micron-sized porous sodium ferrous sulfate / carbon composite cathode material capable of charging and discharging sodium ions and a high-voltage, high-power sodium ion battery or sodium battery containing the same. [Background technology]

[0002] As an energy transmission medium between renewable energy and large-scale energy storage systems, sodium-ion batteries are considered one of the most promising next-generation energy storage systems due to their abundant resource reserves and low cost. However, facing the needs of large-scale energy storage power plants and eco-cars, traditional sodium-ion battery technology cannot meet the application requirements of new technologies, especially the cathode cost and energy density. Therefore, there is an urgent need to develop sodium-ion batteries with low cost, high energy density, high power density, and long cycle life.

[0003] In sodium-ion battery systems, the cathode material largely determines the energy density and cycle stability of the battery device. Compared with sodium iron phosphate, Prussian blue cathodes, and ternary layered oxide cathodes, Alluaudite-type Na 2+2x Fe 2-x (SO 4 ) 3 The material has high elemental reserves, low cost, and a platform with high operating voltage, and is one of the promising sodium-ion battery cathode materials for large-scale application, but its mechanical properties are poor, it is highly polarized at higher rates, its discharge specific capacity is low, and its cycle stability is poor.

[0004] Previous literature has mainly solved the above problems by adjusting the structure of nanoparticles and their composite with carbon materials, but nanomaterials with a large specific surface area reduce the compaction density of the positive electrode and are prone to structural aggregation during the process of sodium ion insertion and removal, which damages the long-term cycle stability of the battery. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above technical problems, the present invention proposes a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material and a sodium-ion battery or sodium battery manufactured therefrom. Using co-precipitation and solid-state calcination methods, micron-sized porous sodium ferrous sulfate / carbon composite particles are prepared, which have excellent structural stability, ionic conductivity, and increased positive electrode compaction density. The sodium ferrous sulfate / carbon composite material can be further doped with metal elements to modify the material, and the assembled rechargeable sodium-ion battery or sodium battery shows excellent rate capability and long cycle stability. [Means for solving the problem]

[0006] The technical means for realizing the present invention are as follows.

[0007] A micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, wherein the particles of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material have a particle size of 2-30 μm, the particles have a porous structure and are composed of densely accumulated primary particles of 80-200 nm, the primary nanoparticles are densely coated with amorphous carbon, and the particle surfaces are covered with a thin layer of reduced graphene, and in the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, the total mass of the graphene / carbon is 4%-18.5% of the mass of the sodium ferrous sulfate / carbon composite positive electrode material.

[0008] In addition, the sodium ferrous sulfate / carbon composite positive electrode material can be doped with a metal element such as Co, Ni, Mn, Cu, or Al.

[0009] A method for preparing a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, comprising the steps of (1) and (2) below: (1) Preparation of precursor by coprecipitation method: Disperse a certain proportion of ethylene glycol and graphene oxide powder in deionized water, apply ultrasonic waves for 15 to 120 minutes, then add a certain proportion of anhydrous sodium sulfate, ferrous sulfate heptahydrate, antioxidants and organic carbon source, and stir for 30 to 120 minutes, then add organic alcohol drop by drop, and stir for 10 to 120 minutes, and then centrifuge the obtained turbid liquid and freeze-dry to obtain a precursor; or Disperse a certain proportion of ethylene glycol and graphene oxide powder in deionized water, apply ultrasonic waves for 15 to 120 minutes, then add a certain proportion of anhydrous sodium sulfate, ferrous sulfate heptahydrate, antioxidants, organic carbon source and metal dopant, and stir for 30 to 120 minutes, then add organic alcohol drop by drop, and stir for 10 to 120 minutes, and then centrifuge the obtained turbid liquid and freeze-dry to obtain a precursor; (2) Preparation of composite positive electrode material by solid-phase calcination: The precursor obtained in step (1) is uniformly ground, then placed in a tubular furnace in an inert atmosphere for pre-sintering, and then the temperature is raised to 300-450°C and calcined for 8-48 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0010] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material is prepared by co-precipitation and solid-state calcination, the dripped organic alcohol acts as a precipitant to promote the co-precipitation of the precursor mixture, and the high viscosity and high surface tension of ethylene glycol inhibit the growth of precipitated particles. The particle size of the resulting composite positive electrode material is 2-30 μm, has a porous structure, and is composed of 80-200 nm primary particles densely accumulated, and the added organic carbon source coats the surface of the precipitated nano-precursor particles with a small molecular structure during the co-precipitation process, and forms a continuous carbon coating layer during the subsequent solid-state calcination process, inhibiting the growth of the crystal particles of sodium ferrous sulfate. At the same time, the gas generated by the thermal decomposition of the organic carbon source helps to build a three-dimensional porous structure in situ within the micron particles, and can provide abundant precipitation sites for insoluble graphene oxide sheets, which are attached or coated on the surface of the micron-sized precursor particles during the continuous stirring process, and then thermally reduced. The surface of the composite positive electrode material particles is uniformly wrapped with a thin layer of reduced graphene, the internal primary particles are densely coated with amorphous carbon, and the total mass of graphene / carbon is 4%-18.5% of the mass of the sodium ferrous sulfate / carbon composite positive electrode material.

[0011] In addition, in the step (1), the mass ratio of deionized water, ethylene glycol, and graphene oxide is 1000:(200-750):(0.1-1), the molar ratio of anhydrous sodium sulfate, ferrous sulfate heptahydrate, an organic carbon source, and an antioxidant is 1:1:(0-0.4):(0.01-0.05), the organic carbon source is one or more of citric acid monohydrate, glucose, and polyethylene glycol, the metal dopant is a sulfate containing a metal ion (including one or more of manganese sulfate, nickel sulfate, cobalt sulfate, copper sulfate, aluminum sulfate, and hydrates thereof), or in the step (1), The mass ratio of deionized water, ethylene glycol, and graphene oxide is 1000:(200-750):(0.1-1), and the molar ratio of anhydrous sodium sulfate, ferrous sulfate heptahydrate, organic carbon source, antioxidant, and metal dopant is 1:(0.9-1):(0-0.4):(0.01-0.05):(0-0.1), the organic carbon source is one or more of citric acid monohydrate, glucose, and polyethylene glycol, and the metal dopant is a sulfate containing a metal ion (including one or more of manganese sulfate, nickel sulfate, cobalt sulfate, copper sulfate, aluminum sulfate, and hydrates thereof).

[0012] In step (1), the antioxidant is one or more of ascorbic acid, pyrrole, and hydroquinone, the volume ratio of the organic alcohol to deionized water is (1.5-5.0):1, the organic alcohol is one or more of isopropyl alcohol, absolute ethanol, n-butanol, tert-butanol, glycerol, and triethylene glycol, the centrifugation speed is 6000-9500 r / min, the centrifugation time is 1-10 minutes, and the lyophilization time is 12-36 hours.

[0013] In step (2), the inert atmosphere is nitrogen gas, argon gas, or argon-hydrogen mixed gas, the pre-sintering process is performed by increasing the temperature to 100-300°C at a rate of 1-5°C / min and holding the temperature for 0.5-3 hours, and the firing process is performed by increasing the temperature to 350-400°C at a rate of 1-3°C / min and holding the temperature for 8-48 hours.

[0014] A sodium ion battery or sodium battery manufactured from a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, comprising a positive electrode piece, a negative electrode piece, an electrolyte, a separator and a case, the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material being the positive electrode, an active material capable of inserting / desorbing sodium ions being the sodium ion battery negative electrode, or metallic sodium being the sodium battery negative electrode, the separator being a modified cellulose acetate separator, a polyethylene or polypropylene microporous membrane, a glass fiber separator or a composite separator thereof, and the electrolyte being a soluble sodium salt organic solution.

[0015] In addition, the positive electrode pieces for sodium batteries are obtained by uniformly mixing a positive electrode material with a conductive agent, a binder and a dispersant and then coating the resulting slurry on a current collector, the current collector being an aluminum foil, the positive electrode pieces for sodium ion batteries are obtained by uniformly mixing a positive electrode material with a conductive agent, a binder and a dispersant and then coating the resulting slurry on a current collector, the current collector being an aluminum foil or a copper foil, and the negative electrode pieces are obtained by uniformly mixing a negative electrode material with a conductive agent, a binder and a dispersant and then coating the resulting slurry on a current collector, the current collector being an aluminum foil or a copper foil.

[0016] In addition, the conductive agent of the sodium ion battery or sodium battery is one or more of acetylene black, Super P, or graphite, the binder of the sodium ion battery or sodium battery is one or more of polytetrafluoroethylene, polyvinylidene fluoride, or styrene butadiene rubber, and the dispersant of the sodium ion battery or sodium battery is one or more of anhydrous ethanol, isopropyl alcohol, or 1-methyl-2-pyrrolidone.

[0017] In addition, the negative electrode of the sodium ion battery is an active material capable of inserting / extracting sodium ions, such as a carbon material, a metal sulfide, a metal oxide, or an alloy compound, and the soluble sodium salt organic solution is obtained by dissolving a sodium salt in an organic solvent, the sodium salt being one or more of sodium hexafluorophosphate, sodium perchlorate, and sodium trifluoromethanesulfonate, and the organic solvent being one or more of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate, diethyl carbonate, diethylene glycol dimethyl ether, 1,3-cyclopentanediol, ethylene glycol dimethyl ether, and triethylene glycol dimethyl ether.

[0018] Preferably, the case of the sodium ion battery or sodium battery is made of organic plastic, aluminum shell, aluminum laminate film, stainless steel, or a composite material thereof.

[0019] Preferably, the shape of the sodium ion battery or sodium battery is button, cylindrical or prismatic. Effect of the Invention

[0020] The advantageous effects of the present invention are as follows: 1. The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material of the present invention has novel and unique morphological features: the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material includes sodium ferrous sulfate / carbon composite material with and / or without metal doping elements, has a micron-sized, porous particle structure, and the stable micron-sized block and effective carbon coating structure improve the structural stability of the composite material. The micron-sized particles of the sodium ferrous sulfate / carbon composite material are composed of nanoscale sodium ferrous sulfate primary nanoparticles assembled in an orderly manner, and the nanoscale particles successfully shorten the permeation path of Na+, reduce the concentration polarization, and increase the ion diffusivity of the material. The multi-layer conductive network constructed by the uniform coating of amorphous carbon and the high dispersion of graphene enhances the electronic conductivity of the composite material. Doping the positive electrode material with appropriate metal cations helps to improve the stability of the positive electrode material surface. Therefore, the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material has the advantages of low electrode cost, abundant raw material reserves, high operating voltage, good rate performance and cycle stability, and the rechargeable sodium-ion battery or sodium battery containing the material has high energy density and high power density.

[0021] 2. The present invention employs a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material as a sodium ion battery or sodium battery positive electrode, which is helpful in increasing the tap density of the positive electrode and the volumetric energy density of the battery. The particles of the sodium ferrous sulfate / carbon composite positive electrode material have a particle size of 2-30 μm, a porous structure, and are composed of an accumulation of 80-200 nm primary particles, with amorphous carbon densely covering the internal primary nanoparticles, and a thin layer of graphene covering the surface of the micron particles, and the three-dimensional conductive network greatly improves the diffusion rate of electrons and ions in the composite material, improving its electrochemical stability. The obtained composite positive electrode material has low cost, abundant raw materials, high working voltage, good rate performance and good cycle stability, and the preparation process is simple and easy to scale up, which is green and environmentally friendly. The rechargeable sodium ion battery or sodium battery containing the material has low cost, high energy density and power density, long cycle stability, and shows a wide market application prospect.

[0022] In order to clearly describe the technical means in the embodiments of the present invention or the prior art, the drawings that need to be used to depict the embodiments or the prior art will be briefly described below. The drawings depicted below are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without any creative activity. [Brief description of the drawings]

[0023] [Figure 1] 1 is an X-ray diffraction (XRD) pattern of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in Example 1. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of the precursor prepared in Example 1. [Diagram 3] 1 is a SEM photograph of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in Example 1. [Figure 4] 1 is a high-resolution SEM photograph of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in Example 1. [Diagram 5] FIG. 2 is a charge / discharge curve diagram of the sodium battery in Example 1. [Figure 6] 1 is a graph showing the rate characteristics of a sodium battery in Example 1. [Figure 7] 1 is a graph showing cycle characteristics of a sodium battery in Example 1. [Figure 8] FIG. 11 is a charge / discharge curve diagram of a sodium ion battery in Example 2. [Figure 9] FIG. 11 is a charge / discharge curve diagram of a sodium ion battery in Example 3. [Figure 10] FIG. 11 is a charge / discharge curve diagram of a sodium battery in Example 4. [Figure 11] FIG. 1 is a SEM photograph of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in Example 5. [Figure 12] FIG. 11 is a charge / discharge curve diagram of a sodium ion battery in Example 5. [Figure 13] FIG. 13 is a charge / discharge curve diagram of a sodium ion battery in Example 6. [Figure 14] FIG. 11 is a charge / discharge curve diagram of a sodium ion battery in Example 7. [Figure 15] FIG. 13 is a charge / discharge curve diagram of a sodium ion battery in Example 8. [Figure 16] FIG. 13 is a charge / discharge curve diagram of a sodium ion battery in Example 9. [Figure 17] FIG. 13 is a charge / discharge curve diagram of a sodium ion battery in Example 12. [Figure 18] FIG. 13 is a charge / discharge curve diagram of a sodium ion battery in Example 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The technical means in the embodiments of the present invention will be described in detail below with reference to the drawings in the embodiments of the present invention, but it goes without saying that the described embodiments are only some of the embodiments of the present invention and do not cover all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without any creative activity are all within the scope of protection of the present invention. EXAMPLES

[0025] The synthesis process of the micron-sized porous sodium ferrous sulfate / carbon composite cathode material used in the present invention is as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 hour, and ultrasonicated for 15 minutes to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4 ), 0.2g of citric acid monohydrate, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 8500 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0026] Figure 1 shows the X-ray diffraction (XRD) pattern of a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material. 2+2x Fe 2-x (SO 4 ) 3The crystallinity is good. The diffraction peak (2theta=32°) shows the highest intensity, indicating that the (240) crystal plane is a facet of the sodium ferrous sulfate crystal. Figure 2 is an SEM photograph of the precursor, showing a relatively regular polyhedral shape. Figure 3 is an SEM photograph of a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, showing that the composite particle masses are dispersed and not aggregated. The side length of the particles of the sodium ferrous sulfate / carbon composite material is about 5 to 7 μm, and the small particles inside are accumulated to form a block structure that contains a wealth of pores. The graphene is a thin layer with a length of 1 to 8 μm that covers the surface of the sodium ferrous sulfate secondary particles. Figure 4 is a high-resolution SEM photograph of a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, showing that the particle size distribution of the sodium ferrous sulfate primary particles is uniform, with a size of 80 to 200 nm, and that the amorphous carbon covers the sodium ferrous sulfate primary particles. The total graphene / carbon mass is 12.3% of the mass of the sodium ferrous sulfate composite.

[0027] The prepared micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material was used as the positive electrode active material, and the positive electrode material was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 70:20:10. 1-Methyl-2-pyrrolidone was used as a dispersant, and the above mixture was mixed uniformly to prepare a slurry, which was then applied onto an aluminum foil. After drying in vacuum at 120°C and cutting, a positive electrode piece with a diameter of 13 mm was obtained. A sodium metal piece was used as the negative electrode (diameter 16 mm), a glass fiber membrane (Whatman GF / D) was used as the separator, and 1M NaClO 4The electrolyte was prepared by dissolving the electrolyte in EC:PC (volume ratio 1:1) (5 wt.% FEC additive). The battery was assembled into a CR2025 button cell in a stainless steel case. The sodium battery assembled by the above process was subjected to a charge-discharge test at room temperature in the potential range of 2.0 to 4.5 V. The charge-discharge curves, rate characteristics, and cycle characteristics are shown in Figures 5, 6, and 7. At a rate of 0.05 C, the discharge platform was about 3.8 V, the specific capacity reached 89 mAh / g, and the battery discharge energy density reached 320 Wh / kg (based on the mass of the positive electrode active material). At a rate of 10 C, the discharge specific capacity could reach 64 mAh / g, and at a rate of 0.5 C, the positive electrode maintained a specific capacity of 70 mAh / g (1 C = 120 mA / g) after 200 cycles. EXAMPLES

[0028] The preparation of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material in this example is the same as in Example 1.

[0029] The prepared micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material was used as the positive electrode active material, and commercially available hard carbon was used as the negative electrode active material. The positive electrode active material was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 70:20:10, and 1-methyl-2-pyrrolidone was used as a dispersant. The negative electrode active material was mixed with acetylene black and sodium carboxymethyl cellulose (CMC) in a mass ratio of 80:10:10, and deionized water was used as a dispersant. The above mixture was uniformly mixed to prepare a slurry, which was then applied to aluminum foil and copper foil, respectively, vacuum dried at 120 °C, and cut to obtain the corresponding positive and negative electrode pieces. The positive and negative electrodes were separated by a glass fiber membrane (Whatman GF / D) and 1M NaClO 4The electrolyte was prepared by dissolving the above in EC:PC (volume ratio 1:1) (with 5 wt.% FEC additive), and the battery was assembled into a rectangular soft-pack battery using an aluminum laminate film as the case. The sodium-ion battery assembled by the above process was subjected to a current charge-discharge test at room temperature in the potential range of 1.0 to 4.0 V. The charge-discharge curves obtained as a result are shown in Figure 8. The discharge platform at a rate of 0.05 C is about 2.8 V, and the discharge specific capacity can reach 65 mAh / g. EXAMPLES

[0030] The preparation of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material in this example is the same as in Example 1.

[0031] The prepared micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material was used as the positive electrode active material, and the ferrous sulfide / carbon composite material was used as the negative electrode active material. The positive electrode active material was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 70:20:10, and 1-methyl-2-pyrrolidone was used as a dispersant. The negative electrode active material was mixed with acetylene black and sodium carboxymethyl cellulose (CMC) in a mass ratio of 80:10:10, and deionized water was used as a dispersant. The above mixture was uniformly mixed to prepare a slurry, which was then applied to aluminum foil and copper foil, respectively, dried in vacuum at 120 °C, and cut to obtain the corresponding positive and negative electrode pieces. The positive and negative electrodes were separated by a glass fiber membrane (Whatman GF / D) and 1M NaCIO 4 The electrolyte was prepared by dissolving the above in EC:PC (volume ratio 1:1) (with 5 wt.% FEC additive), and the battery was assembled into a rectangular soft-pack battery using an aluminum laminate film as the case. The sodium-ion battery assembled by the above process was subjected to a current charge-discharge test at room temperature in the potential range of 1.0 to 4.0 V. The charge-discharge curves obtained as a result are shown in Figure 9. The discharge platform at a rate of 0.05 C is about 2.6 V, and the discharge specific capacity can reach 72 mAh / g. EXAMPLES

[0032] The preparation of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material in this example is the same as in Example 1.

[0033] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in Example 1 was used as the positive electrode active material, and the positive electrode active material was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 70:20:10, and 1-methyl-2-pyrrolidone was used as a dispersant. The mixture was uniformly mixed to prepare a slurry, which was then applied to an aluminum foil, vacuum dried at 120°C, and cut to obtain a positive electrode piece with a diameter of 13 mm. A sodium metal piece was used as the negative electrode (diameter 16 mm), a glass fiber membrane (Whatman GF / D) was used as the separator, and 1M NaClO 4 The electrolyte was prepared by dissolving the above in EC:PC (volume ratio 1:1). A stainless steel case was used as the case and the battery was assembled into a CR2025 button battery. The sodium battery assembled by the above process was subjected to a charge-discharge test at room temperature in the potential range of 2.0 to 4.5 V. The charge-discharge curves are shown in Figure 10. The discharge platform at a rate of 0.05 C is about 3.8 V, and the discharge specific capacity can reach 73 mAh / g. EXAMPLES

[0034] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.01 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (0.5 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 h, and ultrasonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of citric acid monohydrate, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 9000 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0035] FIG. 11 is an SEM photograph of the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example, showing that there are abundant pores in the composite particles, and a thin layer of graphene obviously covers the surface of the sodium ferrous sulfate secondary particles. The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The preparation of the battery was the same as in Example 1. The charge / discharge curves of the assembled sodium ion battery, which were subjected to a charge / discharge test at room temperature in the potential range of 2.0 to 4.5 V, are shown in FIG. 12. The discharge platform at a rate of 0.05 C is about 3.8 V, and the discharge specific capacity can reach 78 mAh / g. EXAMPLES

[0036] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 5 mL of ethylene glycol was added and stirred for 30 min and sonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO4 ), 0.2g of citric acid monohydrate, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 8500 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0037] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery was prepared in the same manner as in Example 1. The charge / discharge curves of the assembled sodium ion battery were shown in FIG. 13, which were obtained by carrying out a charge / discharge test at room temperature in the potential range of 2.0 to 4.5 V. The discharge platform at a rate of 0.05 C was about 3.8 V, and the discharge specific capacity could reach 70 mAh / g. EXAMPLES

[0038] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 15 min and sonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.1 g of citric acid monohydrate, and 0.02 g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 8500 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0039] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery was prepared in the same manner as in Example 1. The charge / discharge curves of the assembled sodium ion battery, which were subjected to a charge / discharge test at room temperature in the potential range of 2.0 to 4.5 V, are shown in FIG. 14. The discharge platform at a rate of 0.05 C is about 3.8 V, and the discharge specific capacity can reach 80 mAh / g. EXAMPLES

[0040] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 30 min and sonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of citric acid monohydrate, and 0.02g of pyrrole were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 9000 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0041] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery was prepared in the same manner as in Example 1. The charge / discharge curves of the assembled sodium ion battery were shown in FIG. 15, which were obtained by carrying out a charge / discharge test at room temperature in the potential range of 2.0 to 4.5 V. The discharge platform at a rate of 0.05 C was about 3.8 V, and the discharge specific capacity could reach 82 mAh / g. EXAMPLES

[0042] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 15 min and sonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of citric acid monohydrate, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 9000 r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 1 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and calcined for 24 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0043] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery preparation was the same as in Example 4. The charge / discharge curves of the assembled sodium ion battery, which were subjected to a charge / discharge test at room temperature in the potential range of 2.0 to 4.5 V, are shown in FIG. 16. The discharge platform at a rate of 0.05 C is about 3.8 V, and the discharge specific capacity can reach 79 mAh / g. EXAMPLES

[0044] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 h, and ultrasonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of polyethylene glycol, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and stirred at room temperature (25 ° C) for 1 hour. 40 mL of isopropyl alcohol was dropped into the above solution to obtain a cloudy suspension. After the dropwise addition, the solution was further stirred for 1 hour. The above cloudy suspension was centrifuged (centrifugation speed 9000 r / min, centrifugation time 5 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200 ° C at a heating rate of 3 ° C / min, pre-sintered for 2 hours, and then the heating rate was further adjusted to 1 ° C / min, the temperature was raised to 350 ° C, and baked for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0045] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery preparation was the same as in Example 1. The assembled sodium ion battery was subjected to a charge-discharge test at room temperature in the potential range of 2.0 to 4.5 V, and the discharge platform at a rate of 0.05 C was about 3.7 V, and the discharge specific capacity could reach 74 mAh / g. EXAMPLES

[0046] The micron-sized porous sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 h, and ultrasonicated for 1 h to form a graphene oxide dispersion. In addition, 1.112 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of polyethylene glycol, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and the mixture was stirred at room temperature (25°C) for 1 hour. 40mL of n-butanol was added dropwise to the solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The cloudy suspension was centrifuged (centrifugation speed 9000r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200°C at a heating rate of 3°C / min, and pre-sintered for 2 hours, and then the heating rate was further adjusted to 1°C / min, the temperature was raised to 350°C, and the mixture was baked for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0047] The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The battery preparation was the same as in Example 1. The assembled sodium ion battery was subjected to a charge-discharge test at room temperature in a potential range of 2.0 to 4.5 V, and the discharge platform at a rate of 0.05 C was about 3.6 V, and the discharge specific capacity could reach 80 mAh / g. EXAMPLES

[0048] The micron-sized porous aluminum-doped sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 h, and ultrasonicated for 1 h to form a graphene oxide dispersion. In addition, 1.0564 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.0889 g of aluminum sulfate octahydrate, 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of polyethylene glycol, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and the mixture was stirred at room temperature (25°C) for 1 hour. 40mL of n-butanol was added dropwise to the solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The cloudy suspension was centrifuged (centrifugation speed 9000r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200°C at a heating rate of 3°C / min, and pre-sintered for 2 hours, and then the heating rate was further adjusted to 1°C / min, the temperature was raised to 350°C, and the mixture was baked for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0049] The micron-sized porous aluminum-doped sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The preparation of the battery was the same as in Example 1. The assembled sodium ion battery was subjected to a charge-discharge test at room temperature in a potential range of 2.0 to 4.5 V. The charge-discharge curve is shown in FIG. 17. After 30 cycles at a 0.1 C rate, the discharge specific capacity reached 74 mAh / g, and the discharge platform was about 3.5 V. EXAMPLES

[0050] The micron-sized porous copper-doped sodium ferrous sulfate / carbon composite cathode material was prepared as follows: 0.02 g of graphene oxide dry powder was weighed out and dispersed in 20 mL of deionized water (1 mg / mL), then 10 mL of ethylene glycol was added and stirred for 1 h, and ultrasonicated for 1 h to form a graphene oxide dispersion. In addition, 1.0564 g of ferrous sulfate heptahydrate (FeSO 4 -7H 2 O), 0.0499 g of copper sulfate pentahydrate, 0.5682 g of anhydrous sodium sulfate (Na 2 SO 4), 0.2g of polyethylene glycol, and 0.02g of ascorbic acid were weighed out and dissolved in the graphene oxide dispersion liquid, and the mixture was stirred at room temperature (25°C) for 1 hour. 40mL of n-butanol was added dropwise to the solution to obtain a cloudy suspension. After the dropwise addition, the mixture was further stirred for 1 hour. The cloudy suspension was centrifuged (centrifugation speed 9000r / min, centrifugation time 3 minutes), the obtained solid was frozen in liquid nitrogen, and then freeze-dried for 36 hours to obtain a precursor. The precursor was uniformly crushed, transferred to a ceramic container, placed in an oxygen atmosphere tubular furnace, the temperature was raised to 200°C at a heating rate of 3°C / min, and pre-sintered for 2 hours, and then the heating rate was further adjusted to 1°C / min, the temperature was raised to 350°C, and the mixture was baked for 12 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

[0051] The micron-sized porous copper-doped sodium ferrous sulfate / carbon composite positive electrode material prepared in this example was used as the positive electrode material, and metallic sodium was used as the negative electrode. The preparation of the battery was the same as in Example 1. The assembled sodium ion battery was subjected to a charge-discharge test at room temperature in a potential range of 2.0 to 4.5 V. The charge-discharge curve is shown in FIG. 18. After 30 cycles at a 0.1 C rate, the discharge specific capacity reached 67 mAh / g, and the discharge platform was about 3.6 V.

[0052] The above are preferred embodiments only for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto. Various modifications, equivalent replacements, and improvements can be made within the scope that does not deviate from the spirit and principles of the present invention, and are considered to be included in the scope of protection of the present invention.

Claims

1. 1. A micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, the particles of which have a particle size of 2-30 μm, the particles having a porous structure and consisting of densely packed primary particles of 80-200 nm, the primary nanoparticles being densely coated with amorphous carbon, and the particle surfaces being covered with a thin layer of reduced graphene, the total mass of the graphene / carbon in the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material being 4%-18.5% of the mass of the sodium ferrous sulfate / carbon composite positive electrode material.

2. The micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material according to claim 1, characterized in that it can be doped with metal elements such as Co, Ni, Mn, Cu or Al.

3. A method for preparing the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material according to claim 1 or 2, comprising the steps of: (1) Preparing the precursor by co-precipitation method: dispersing a certain proportion of ethylene glycol and graphene oxide powder in deionized water, applying ultrasonic waves for 15-120 minutes, then adding a certain proportion of anhydrous sodium sulfate, ferrous sulfate heptahydrate, antioxidants and organic carbon source, stirring for 30-120 minutes, then adding organic alcohol drop by drop, stirring for 10-120 minutes, and then centrifuging the resulting turbid liquid and freeze-drying to obtain the precursor; or dispersing a certain proportion of ethylene glycol and graphene oxide powder in deionized water, applying ultrasonic waves for 15-120 minutes, then adding a certain proportion of anhydrous sodium sulfate, ferrous sulfate heptahydrate, antioxidants, organic carbon source and metal dopant, stirring for 30-120 minutes, then adding organic alcohol drop by drop, stirring for 10-120 minutes, and then centrifuging the resulting turbid liquid and freeze-drying to obtain the precursor; (2) Preparation of a composite positive electrode material by a solid-phase calcination method: The precursor obtained in the above step (1) is uniformly ground, then pre-sintered in a tubular furnace in an inert atmosphere, and then heated to 300-450° C. and calcined for 8-48 hours to obtain a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material.

1. A method for preparing a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material, comprising:

4. In the step (1), the mass ratio of deionized water, ethylene glycol, and graphene oxide is 1000:(200-750):(0.1-1), the molar ratio of anhydrous sodium sulfate, ferrous sulfate heptahydrate, an organic carbon source, and an antioxidant is 1:1:(0-0.4):(0.01-0.05), the organic carbon source is one or more of citric acid monohydrate, glucose, and polyethylene glycol, the metal dopant is a sulfate containing a metal ion (including one or more of manganese sulfate, nickel sulfate, cobalt sulfate, copper sulfate, aluminum sulfate, and hydrates thereof), or a mass ratio of anhydrous sodium sulfate, ferrous sulfate heptahydrate, organic carbon source, antioxidant and metal dopant is 1:(0.9-1):(0-0.4):(0.01-0.05):(0-0.1), the organic carbon source is one or more of citric acid monohydrate, glucose and polyethylene glycol, and the metal dopant is a sulfate containing metal ion (including one or more of manganese sulfate, nickel sulfate, cobalt sulfate, copper sulfate, aluminum sulfate and their hydrates).

5. The method for preparing micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material according to claim 3, characterized in that in step (1), the antioxidant is one or more of ascorbic acid, pyrrole, and hydroquinone, the volume ratio of the organic alcohol to deionized water is (1.5-5.0):1, the five organic alcohols are one or more of isopropyl alcohol, absolute ethanol, n-butanol, tert-butanol, glycerol, and triethylene glycol, the centrifugation speed is 6000-9500 r / min, the centrifugation time is 1-10 min, and the lyophilization time is 12-36 h.

6. The method for preparing a micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material according to claim 3, characterized in that in step (2), the inert atmosphere is nitrogen gas, argon gas or argon-hydrogen mixed gas, the pre-sintering process is to increase the temperature to 100-300°C at a heating rate of 1-5°C / min and hold for 0.5-3 hours, and the calcination process is to increase the temperature to 350-400°C at a heating rate of 1-3°C / min and hold for 8-48 hours.

7. 3. A sodium ion battery or sodium battery manufactured from the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material according to claim 1 or 2, comprising a positive electrode piece, a negative electrode piece, an electrolyte, a separator and a case, characterized in that the micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material is used as the positive electrode, an active material capable of inserting / desorbing sodium ions is used as the sodium ion battery negative electrode, or metallic sodium is used as the sodium battery negative electrode, the separator is a modified cellulose acetate separator, a polyethylene or polypropylene microporous membrane, a glass fiber separator or a composite separator thereof, and the electrolyte is a soluble sodium salt organic solution.

8. The sodium ion battery or sodium battery according to claim 7, characterized in that the positive electrode pieces of the sodium battery are obtained by uniformly mixing a positive electrode material with a conductive agent, a binder and a dispersant and then coating a current collector with the obtained slurry, the current collector being an aluminum foil, the positive electrode pieces for the sodium ion battery are obtained by uniformly mixing a positive electrode material with a conductive agent, a binder and a dispersant and then coating a current collector with the obtained slurry, and the negative electrode pieces are obtained by uniformly mixing a negative electrode material with a conductive agent, a binder and a dispersant and then coating a current collector with the obtained slurry, the current collector being an aluminum foil or a copper foil.

9. The sodium ion battery or sodium battery according to claim 8, characterized in that the conductive agent is one or more of acetylene black, Super P, or graphite, the binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, or styrene butadiene rubber, and the dispersant is one or more of anhydrous ethanol, isopropyl alcohol, or 1-methyl-2-pyrrolidone.

10. The sodium ion battery or sodium battery according to claim 7, characterized in that the active material capable of inserting / extracting sodium ions includes a carbon material, a metal sulfide, a metal oxide, and an alloy compound, the soluble sodium salt organic solution is obtained by dissolving a sodium salt in an organic solvent, the sodium salt being one or more of sodium hexafluorophosphate, sodium perchlorate, and sodium trifluoromethanesulfonate, and the organic solvent being one or more of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate, diethyl carbonate, diethylene glycol dimethyl ether, 1,3-cyclopentanediol, ethylene glycol dimethyl ether, and triethylene glycol dimethyl ether.

Citation Information

Patent Citations

  • Na2Fe(SO4)2 / C electrode material jointly prepared by graphene and / or acetylene black, preparation method thereof and prepared battery

    CN110336021A

  • Nonaqueous secondary battery, and positive electrode active material for nonaqueous secondary batteries and method for producing same

    WO2017119171A1

Cited By

  • Positive electrode active material and method for manufacturing the same, positive electrode plate, battery and electrical equipment

    JP2026528335A

  • Ferrous sodium sulfate positive electrode material and method for producing the same, positive electrode sheet, and secondary battery

    JP2026529029A

  • Positive electrode active material and method for manufacturing the same, positive electrode plate, battery and electrical equipment

    JP7920478B2